Enforcement of intellectual property rights and dispute settlement - Professor Dr. P.S. Sangal, (Fakulti Undang - Undang, 2000)

(untitled)
This article examines the provisions of part III (Enforcement of Intellectual Property Rights) Articles 41-61 Part V (Dispute Prevention and Settlement) Articles 63-64 of the Agreement On Trade-Related Aspects of Intellectual Property Rights (TRIPS). This agreement besides laying down substantive requirements in regard to Intellectual Property Rights (IRPRs), also prescribes in the aforesaid provisions the procedural safeguards about the enforcement of those substantive standard. Discussing the requirement under Article 51 of TRIPS about Border Measures, the article shows as to how Malaysia implements this requirement through section 39 or the Copyright Act 1987 under which copyright (Notice of Prohibition of Impact) Regulation 1987 has also been promulgated